Extreme managers, extreme workplaces: Capitalism, organizations and corporate psychopaths. (July 2015) - Boddy, Clive; Miles, Derek; Sanyal, Chandana; Hartog, Mary
This article reports on qualitative research carried out in England in 2013. Participants were five organizational directors and two senior managers who had worked with six corporate psychopaths, as determined by a management psychopathy measure. The corporate psychopaths reported on displayed consistency in their approach to management. This approach was marked by high levels of abusive control. The corporate psychopaths were seen as being organizational stars and as deserving of awards by those above them, while they simultaneously subjected those below them to extreme behaviour, including bullying, intimidation and coercion. The corporate psychopaths also engaged in extreme forms of mismanagement characterized by poor personnel management, directionless leadership, mismanagement of resources and fraud.